The impact of environmentally-specific servant leadership on organizational green performance: The mediating role of green creativity - Hou, Hong; Gai, Ruizhi; An, Li (Frontiers in Psychology, 2023)
Due to the increasingly prominent environmental problems caused by excessive carbon dioxide emissions, many countries have put forward higher requirements for the green development of enterprises. Therefore, how to improve the green performance of enterprises has become a hot issue. Based on the social learning perspective, we examine the impact of environmentally-specific servant leadership on organizational green performance and test the mediating role of green creativity and the moderating role of power distance orientation. We test the theoretical framework by means of a questionnaire survey with a research sample of employees and their leaders working in the eastern coastal region of China. The results of the study suggest that: environmentally-specific servant leadership has a positive influence on organizational green performance; green creativity plays a mediating role between environmentally-specific servant leadership and organizational green performance; power distance orientation plays a moderating role between environmentally-specific servant leadership and green creativity; specifically, the higher the power distance orientation, the more significant the influence of environmentally-specific servant leadership on employees’ green creativity. This study enriches the research on environmentally-specific servant leadership and proposes a new perspective on how to improve green performance in organizations.